2018
DOI: 10.3390/nu10020224
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Optimal Post-Exercise Muscle Protein Remodeling in Physically Active Adults through Whole Food Consumption

Abstract: Dietary protein ingestion is critical to maintaining the quality and quantity of skeletal muscle mass throughout adult life. The performance of acute exercise enhances muscle protein remodeling by stimulating protein synthesis rates for several hours after each bout, which can be optimized by consuming protein during the post-exercise recovery period. To date, the majority of the evidence regarding protein intake to optimize post-exercise muscle protein synthesis rates is limited to isolated protein sources. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 108 publications
2
26
0
Order By: Relevance
“…As protein and protein supplements are widely advertised and recommended to athletes, this is an important gap in the research that should be addressed. Future research should also be sure to compare the effects of different protein sources as both isolated supplements as well as in their whole-food form as the matrix of the whole food has been shown to play an important role in the anabolic response to exercise and may alter effects based on factors such as the type and amount of fat (106,107). Additionally, it would be interesting to know whether supplementation of plant-based proteins with amino acids such as leucine, lysine, and methionine, which is a strategy that has been shown by a couple studies to augment the anabolic effect of plant proteins (105), alters the effect of these proteins on the gut microbiome.…”
Section: Effects Of Supplements and Dietary Patterns On The Gut Micromentioning
confidence: 99%
“…As protein and protein supplements are widely advertised and recommended to athletes, this is an important gap in the research that should be addressed. Future research should also be sure to compare the effects of different protein sources as both isolated supplements as well as in their whole-food form as the matrix of the whole food has been shown to play an important role in the anabolic response to exercise and may alter effects based on factors such as the type and amount of fat (106,107). Additionally, it would be interesting to know whether supplementation of plant-based proteins with amino acids such as leucine, lysine, and methionine, which is a strategy that has been shown by a couple studies to augment the anabolic effect of plant proteins (105), alters the effect of these proteins on the gut microbiome.…”
Section: Effects Of Supplements and Dietary Patterns On The Gut Micromentioning
confidence: 99%
“…The coingestion of foods that are not necessarily high in protein may still impact the total protein intake, the amino acid profile of the meal, protein digestion and absorption kinetics, hormonal response, and micronutrient intake. Such factors can potentially modulate the MPS response to feeding, but their individual contributions are difficult to predict [30].…”
Section: Mixed Meal Compositionmentioning
confidence: 99%
“…As previously discussed, fat co-ingestion may augment the post-exercise MPS response to protein ingestion [55]. Furthermore, several micronutrients that are present primarily in the yolk, such as vitamin A, vitamin D, vitamin E, zinc, selenium and cholesterol, are potential candidates that may be responsible for the greater anabolic response to feeding [48,61]. In addition, the coingestion of an amylopectin/chromium complex has recently been shown to augment the post-exercise MPS response to the ingestion of a suboptimal amount of protein [62].…”
Section: Macronutrients Versus Mealsmentioning
confidence: 95%
“…For example, early work by Bergstrom and Hultman demonstrated that an intravenous glucose infusion reduced muscle glycogen breakdown by ~20% during 60 min of cycling [5]. While many subsequent studies have observed a lower rate of muscle glycogen utilization when carbohydrate was ingested during prolonged exercise [9,[41][42][43][44][45][46], others have failed to confirm these findings [47][48][49][50][51]. For example, Coyle et al observed an increase in time to fatigue when subjects ingested carbohydrate during exercise compared to a placebo, despite no differences in muscle glycogen utilization between the treatments [47].…”
Section: Carbohydrates During Exercise As An Ergogenic Aidmentioning
confidence: 99%
See 1 more Smart Citation